Die Missionstation Makkovik von zugefrorener Bucht aus : [ca. 1901] - Schmitt, Christian, 1868-1933. (2001)
Black and white photograph of the Moravian church and mission building at Makkovik with an Inuit man and dogs in foreground, circa 1901. Black and white photograph of the Moravian church and mission building at Makkovik with an Inuit man and dogs in foreground, circa 1901.